Comparison of Nutritional Parameters among Adult and Elderly Hemodialysis Patients - Gülperi Çelik, Bahar Oc, Inci Kara, Mümtaz Yılmaz, Ali Yuceaktas, Seza Apiliogullari (International Journal of Medical Sciences, 2011)
Aim: The aim of this study was to compare the nutritional biochemical parameters, prealbumin levels, and bioimpedance analysis parameters of adult and elderly hemodialysis (HD) patients. Methods: This prospective cross-sectional study included 50 adult HD patients (42.0 % female). Nutritional status was assessed by post-dialysis multifrequency bioimpedance analysis (BIA), serum prealbumin and other nutritional biochemical parameters. Results: Mean age of patients was 57.4±15.1 years (range: 30-83 years) and mean dialysis duration was 68.3 ± 54.5 months (range: 3-240 months). When the patients were divided into two groups according to age of patients (<65 and ≥65), prealbumin (p=0.003), blood urea nitrogen (BUN) (p=0.000), serum creatinine (p=0.013), albumin (p=0.016), protein catabolic rate per normalized body weight (nPCR) (p=0.001), intracellular water (ICW)/total body weight (0.003) , body fat mass (p00.000), lean body mass (p=0.031), lean dry mass (p=0.001), illness marker (p=0.005), basal metabolism (p=0.007), body mass index (BMI) (p=0.028), body fat mass index (BFMI) (p=0.000), fat free mass index (FFMI) (p=0.040) values were significantly different between the groups. In the elderly patients (age ≥65), body fat mass, illness marker, BMI, BFMI were higher compared to adult patients (age <65). Additionally, in the elderly patients, prealbumin, BUN, creatinine, albumin, nPCR, ICW/ total body weight, lean body weight, lean dry weight, basal metabolism and FFMI were lower than adult patients. Conclusions: Our results indicate that BFMI were higher, albumin, prealbumin, nPCR and lean body mass and FFMI were lower in elderly patients compared to adults. These results imply that elderly HD patients may be prone sarcopenic obesity and may require special nutritional support.